2018
DOI: 10.1101/388421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective pressures on human cancer genes along the evolution of mammals

Abstract: Abstract:Cancer is a disease of the genome caused by somatic mutation and subsequent clonal selection. Several genes associated to cancer in humans, hereafter cancer genes, also show evidence of (germline) positive selection among species. Taking advantage of a large collection of mammalian genomes, we systematically looked for statistically significant signatures of positive selection using dN/dS models in a list of 430 cancer genes. Among these, we identified 63 genes under putative positive selection in mam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…Because natural selection may act differently on somatic mutations compared with germline mutations ( Vicens and Posada 2018 ), we considered an alternative subdivision of tumor suppressor genes depending on whether the cancer-associated mutations only occurred somatically, only in the germline, or both. When we compared human cancer gene duplications across the eutherian superorders, we found that the genomes of euarchontoglires ( n = 8) contained a higher median oncogene and germline tumor suppressor gene duplication, whereas xenarthran genomes ( n = 2) contained a higher median duplication of genes that are both tumor suppressors and oncogenes, as well as a higher median duplication when all tumor suppressor genes were classified together ( supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because natural selection may act differently on somatic mutations compared with germline mutations ( Vicens and Posada 2018 ), we considered an alternative subdivision of tumor suppressor genes depending on whether the cancer-associated mutations only occurred somatically, only in the germline, or both. When we compared human cancer gene duplications across the eutherian superorders, we found that the genomes of euarchontoglires ( n = 8) contained a higher median oncogene and germline tumor suppressor gene duplication, whereas xenarthran genomes ( n = 2) contained a higher median duplication of genes that are both tumor suppressors and oncogenes, as well as a higher median duplication when all tumor suppressor genes were classified together ( supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that pathways associated with hereditary cancers, which are caused by germline mutations, may face different constraints than those associated with sporadic cancers. Vicens and Posada (2018) analyzed ratios of the proportion of nonsynonymous substitutions per site to the proportion of synonymous substitutions per site in human cancer genes across mammals and found evidence for relaxed selective constraint in cancer genes with germline mutations relative to those with somatic mutations. Thus, there may be stronger purifying selection acting on pathways associated with highly deleterious sporadic cancers, which would reduce the fixation rate of copy number variants related to those pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that cancer suppression could be enhanced by altering a preexisting gene via amino acid changes, which would leave a signal of positive selection. The extent to which such enhancement could mitigate against the effect of somatic mutations is unclear; however, evidence of positive selection in cancer‐related genes has been reported in a number of studies (Morgan et al., 2012; O’Connell, 2010; Tollis et al., 2019; Vicens & Posada, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…PALB2 may therefore also have experienced positive selection for this reason. However, similarly to other genes involved in DNA repair, PALB2 is also under positive selection in other mammals 76 , suggesting it does not play an important role only in bats. Large-scale scans for positive selection across mammals may help resolve the different roles of tumor suppressor genes in cancersusceptible and cancer-resistant lineages, and the evolutionary history of these genes.…”
Section: Selection Of Cancer-associated Genes In the Bat Ancestormentioning
confidence: 99%